Biodiesel production via two steps catalyzed process : the study on effect of temperature and catalyst weight percent to the biodiesel yield, FFA content and acid value. - Amminatul Farhayu, Abdul Talib (2008)
In this study, the effects of temperature and catalyst weight percent to the biodiesel yield, FFA content and acid value were studied. The biodiesel is produced by two-steps catalyzed process. The essential part of the process is the transesterification of waste cooking oil (WCO) with methanol in present of catalyst, to yield methyl ester as the main product and glycerin as the by-product. In the acid treatment or the acid- catalyzed esterification, the temperature is set at 95°C, acid catalyst of 2%w/wH2SO and methanol to waste cooking oil of 10:1. For the alkali-catalyzed transesterification, the range of temperature is 40°C-80°C, the alkali c atalyst weight percent is varied from 0.2 to 1.0%wNaOH/wWCO. The ultrasonic wave and ratio of methanol to waste cooking was fixed at 32MHz and 6:1 respectively. The biodiesel product is then analyzed by titration to check the FFA content and the acid value. The best temperature and alkali catalyst weight percent was found at 70° C and 1.0%wNaOH/wWCO correspondingly. The total reduction of FFA content after acid treatment was 36.92%. The two steps catalyzed process is preferable for raw material that has high content of FFA such as waste cooking oil.